RANCANG BANGUN GAME ANDROID BERTEMA PEMILU DENGAN ENGINE CONSTRUCT 2 BERBASIS HTML 5 - Sheedy Sheedy (Institut Bisnis dan Informatika Kwik Kian Gie, 2015)
Development in technology is amazingly fast, especially in mobile technology. With the newest mobile gadgets, we changed our lifestyle. One of them is the usage of smartphone as our daily entertainment device. Smartphone offer a lot of entertainment such as gaming which is playable every time and everywhere. There are a lot of themes in a game, but one of them which is election is less popular than the others. This thing is obvious since election is considered as too formal and boring. Also, making an Android game in HTML 5 language is considered not good as the native language itself. This Android Game is designed using Construct 2 engine with HTML 5 as it main language. Methods used in this game development are direct presidential election observation in local area. The result of this development is a game application which has many elements in it. This game offer a large selection of stages and other features such as sharing score to social networking websites in order to attract the interest of the others. Conclusion of this game development is that a game with presidential election theme can be an interesting game, also HTML 5 can be used as main programing language for Android games without losing in performance compared to the games using native language.Keywords: game, HTML 5, presidential election.